Synthesis of LaMnO3 perovskite by the gel combustion method at low temperature - Đại, Lưu Minh; Dũng, Nguyễn Xuân (Vietnam Journal of Chemistry, 2012)
LaMnO3 has been synthesised at low temperature (600oC) by the combustion of gel prepared from polyvinyl alcohol (PVA) and metal nitrates. LaMnO3 characterization is examined by X-ray diffraction (XRD), thermogravimetric and differential thermal analysis (TG-DTA), transmission  electron microscopy (TEM) and BET (Brunaure-Emmet-Teller) measurements. The obtained  sample under optional preparative conditions  has nano scale with large specific square area.